MANDARIN MADE EASY THROUGH ENGLISH - Lim Hong Swan; Yeoh Li Cheng (Penerbit UTHM, 2009)
This book is intended for learners who do not have a formal background in Mandarin language. It is designed to train learners in order to acquire the basic skills to communicate effectively in the language. Learners can start mastering Mandarin through Hanyu Pinyin i.e. a phonetic transcription system using a modified Latin alphabet. The book integrates the aspects of phonetics, conversational settings and vocabulary. It also aimed not only at allowing learners to familiarize themselves with Mandarin, but also enjoy learning it. A variety of topics are laid out over 5 chapters which include everyday situations and simple dialogues like phonetics, numbers, clock time & calendar time, daily expressions and forms of address.